Computerized Operator Support System for Nuclear Power Plant Hybrid Main Control Room. (November 2019) - Lew, Roger; Boring, Ronald L.; Ulrich, Thomas A.
A Computerized Operator Support System (COSS) is an operator assistive technology that aids operators in monitoring processes to detect off-normal conditions, diagnose plant faults, predict future plant states, recommend mitigation alternatives, and select appropriate mitigation actions. The COSS works in collaboration with an advanced prognostics system called PROAID. The COSS provides a human-machine interface to help operators maintain situation awareness and detect faults earlier than would be possible using conventional control room technologies at nuclear power plants. Here we describe a third-iteration of efforts to develop and validate the COSS. The COSS has now been implemented as a prototype system for a full-scope nuclear power plant simulator. To date, two studies involving three licensed reactor crews were conducted to evaluate the COSS. Here we capture insights into the development of COSS as well as operator feedback and future development guidance derived from the operator-in-the-loop simulator studies.